RETRACTED: Santacruzamate A Ameliorates AD-Like Pathology by Enhancing ER Stress Tolerance Through Regulating the Functions of KDELR and Mia40-ALR in vivo and in vitro - Chen, Lei; Liu, Yue-cheng; Tan, Hui; Zhang, Yuan; Xu, Ji; Liu, Wen-lan; Li, Zong-yang; Li, Wei-ping (Frontiers in Cellular Neuroscience, 2019)
Aggregated amyloid-β protein (Aβ) and Aβ-induced neuronal apoptosis have been implicated as critical factors in the pathophysiology of Alzheimer’s disease (AD). Certain preclinical results have indicated that the increased accumulation of protein aggregates in AD-affected neurons activates the unfolded protein response (UPR), a pathological phenomenon, which predominantly mediates the aberrant endoplasmic reticulum (ER) stress and apoptotic cascades in neuronal cells. In the present study, we confirmed that Santacruzamate A (STA, a natural product isolated from a Panamanian marine cyanobacterium) attenuates Aβ25–35-induced toxicity in PC12 cells and rescues cognitive deficits in APPswe/PS1dE9 mice by enhancing ER stress tolerance. We first demonstrated the anti-apoptotic effects of STA by evaluating caspase-3 activity, annexin V/propidium iodide staining, and terminal deoxynucleotidyl transferase dUTP nick end labelling staining. Behavioural testing of STA-treated APPswe/PS1dE9 mice showed that the pronounced memory impairments were ameliorated and that the consolidated memories were stably maintained over a 2-week period. The mechanistic studies provided evidence that STA inhibited Aβ25–35-induced UPR and ER stress by regulating the ER retention signal (KDEL) receptor, which reinforced the retention of resident chaperones in the ER lumen. Furthermore, STA regulated the expression of the mitochondrial intermembrane space assembly protein 40 (Mia40) and augmenter of liver regeneration (ALR), which ultimately attenuated the mitochondrial fission and apoptosis pathways. Together, our present findings suggest that the KDEL receptor and Mia40-ALR play a role in mitigating Aβ25–35-induced neurotoxicity, which might in turn positively regulate learning and memory. These observations support that STA may be a promising agent for reversing the progression of AD.